2015
DOI: 10.4103/0019-509x.178409
|View full text |Cite
|
Sign up to set email alerts
|

Hypofractionated radiotherapy for localized prostate cancer using three-dimensional conformal radiotherapy technique: 3 years toxicity analysis

Abstract: A 57Gy in 19 daily fraction radiotherapy schedule using 3D conformal radiotherapy for the definitive treatment of localized prostate cancer has acceptable early and late toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…White et al [41] evaluated 90 patients treated with 57 Gy in 17 fz of 3Gy and have reported acute genitourinary toxicity G 1, 2 and 3 to 58.6%, 10% and 1.1% respectively; acute gastrointestinal toxicity to 75.6%, 9% and 0% respectively. Grade 1, 2 and 3 GU and GI late toxicity were 47.3%, 2.4%, 0%, and 40%, 9.3% and 4.7% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…White et al [41] evaluated 90 patients treated with 57 Gy in 17 fz of 3Gy and have reported acute genitourinary toxicity G 1, 2 and 3 to 58.6%, 10% and 1.1% respectively; acute gastrointestinal toxicity to 75.6%, 9% and 0% respectively. Grade 1, 2 and 3 GU and GI late toxicity were 47.3%, 2.4%, 0%, and 40%, 9.3% and 4.7% respectively.…”
Section: Discussionmentioning
confidence: 99%